2006
DOI: 10.1016/j.jacc.2005.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Ventricular Arrhythmia Inducibility for Subsequent Ventricular Tachycardia or Ventricular Fibrillation in Multicenter Automatic Defibrillator Implantation Trial (MADIT) II Patients

Abstract: In the MADIT II study patients, inducibility was associated with an increased likelihood of VT. Noninducible MADIT II study subjects using this electrophysiologic protocol had a considerable VT event rate and a higher VF event rate than inducible patients. Induction of polymorphic VT or VF, even with double extrastimuli, appears less relevant than induction of monomorphic VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(117 citation statements)
references
References 39 publications
8
106
1
2
Order By: Relevance
“…Various electric measures of arrhythmic risk, such as T-wave alternans, signal-averaged ECG, and electrophysiological study, have not demonstrated adequate or consistent discriminatory power. 4,5 Paradoxically, the mortality reduction benefit of primary prevention ICDs was established only when risk stratification was based on measures of left ventricular dysfunction and functional class (left ventricular ejection fraction Ͻ30% after myocardial infarction in MADIT II or left ventricular ejection fraction Ͻ35% with New York Heart Association class II to III in SCD-HeFT) rather than direct measures of arrhythmic risk.…”
Section: Article See P 835mentioning
confidence: 99%
“…Various electric measures of arrhythmic risk, such as T-wave alternans, signal-averaged ECG, and electrophysiological study, have not demonstrated adequate or consistent discriminatory power. 4,5 Paradoxically, the mortality reduction benefit of primary prevention ICDs was established only when risk stratification was based on measures of left ventricular dysfunction and functional class (left ventricular ejection fraction Ͻ30% after myocardial infarction in MADIT II or left ventricular ejection fraction Ͻ35% with New York Heart Association class II to III in SCD-HeFT) rather than direct measures of arrhythmic risk.…”
Section: Article See P 835mentioning
confidence: 99%
“…In the MADIT II trial, patients with CAD and severely reduced LVEF (r30%) were randomized to ICD implantation or conventional therapy without requiring PES [9]. Nonetheless, PES was encouraged by the study committee, and 82% of the patients in the ICD arm underwent PES [12]. In the subgroup analysis, appropriate ICD therapy was more common in the inducible patients, but was still high in the non-inducible group (25.5% at two years).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying VF initiation are still poorly understood and how stable VT degenerates into VF is still not clear (Weiss et al 2000). Clinical trials have provided important information that tests used to induce VT in patients with prior MI and low left ventricular ejection fraction would predict future VT events but not necessary VF in patients with implantable cardioverter defibrillators (Daubert et al 2006). VF can arise without going through a period of stable VT and hence its initiation requires better understanding.…”
Section: Ventricular Arrhythmia Mechanisms and Sympathetic Activationmentioning
confidence: 99%